The psychological impact of the COVID emergency on Italian nursing homes staff and the effectiveness of eye movement desensitization and reprocessing - Faretta, Elisa; Maslovaric, Giada; Garau, M. Ignazia; Marmondi, Gabriella; Piras, Laura; Rezzola, Simona; Incerti, Alessia; Nardoni, Anna; Pagani, Marco; Gallina, Eugenio (Frontiers in Psychology, 2022)
Residential nursing homes were particularly badly affected by the first wave of COVID-19, with large numbers of their frail person getting infected with COVID-19 and dying. The staff in these structures were catapulted into a reality very different from what they were used to. They had to adapt the way they used to take care of their patients in a very short space of time and in a scenario that was continually changing. In this manuscript we describe the subjective experience of staff in a number of Italian nursing homes during the first wave of the COVID-19 pandemic; and we report data showing the effectiveness of the Eye Movement Desensitization and Reprocessing (EMDR) treatment provided to support them during this Pandemic.